Successful lung transplantation in an HIV seropositive patient with desquamative interstitial pneumonia: a case report - Shaun Ong; Robert D Levy; John Yee; Nilu Partovi; Andrew Churg; Philippe Roméo; Jean Chalaoui; Roland Nador; Alissa Wright; Hélène Manganas; Christopher J Ryerson (BMC Pulmonary Medicine, 2018)
Abstract Background Until recently, lung transplantation was not considered in patients with human immunodeficiency virus (HIV). HIV seropositive patients with suppressed viral loads can now expect long-term survival with the advent of highly active antiretroviral therapies (HAART); however, HIV remains a relative contraindication to lung transplantation. We describe, to our knowledge, the first HIV seropositive lung transplant recipient in Canada. We also review the literature of previously reported cases of solid-organ transplantation in patients with HIV with a focus on immunosuppression considerations. Case presentation A 48-year old man received a bilateral lung transplant for a diagnosis of desquamative interstitial pneumonia (DIP) attributed to cigarette and cannabis smoking. His control of HIV infection pre-transplant was excellent on HAART, and he had no other contraindications to lung transplantation. The patient underwent bilateral lung transplantation using basiliximab, methylprednisolone, and mycophenolate mofetil (MMF) as induction immunosuppression. He was maintained on MMF, prednisone, and tacrolimus thereafter, and restarted his HAART regimen immediately post-operatively. His post-transplant course was complicated by Grade A1 minimal acute cellular rejection, as well as an enterovirus/rhinovirus graft infection. Despite these complications, his functional status and control of HIV infection remain excellent 24 months post-transplant. Conclusions Our patient is one of only several HIV seropositive lung transplant recipients reported globally. With growing acceptance of transplantation in this population, there is a need for clarification of prognosis post-transplantation, as well as optimal immunosuppression regimens for these patients. This case report adds to the recent literature that suggests HIV seropositivity should not be considered a contraindication to lung transplantation, and that post-transplant patients with HIV can be managed safely with basiliximab, tacrolimus, MMF and prednisone.